(untitled) (The Pakistan Development Review, 2025)
Cities in Pakistan are increasingly faced with problems of erratic supply of piped water and unsafe and declining levels of groundwater. Additionally, over one-third (35 to 40 percent) of piped water is wasted through leakages and theft in the water distribution networks.[1] By 2050, the country’s urban population is expected to double in size (from 81 million in 2022 to 160 million in 2050 or from 37.7 percent of the total population to 52.2 percent) (see table 1). Providing water for these citizens is a challenging task; finding money to pay for the provision of that water is at least as daunting. Urban water tariffs are low and infrequently adjusted, even with current efforts at reform.